Clearance of peripheral nerve misfolded mutant protein by infiltrated macrophages correlates with motor neuron disease progression - Wataru Shiraishi (Nature Portfolio, 2021)
Abstract Macrophages expressing C–C chemokine receptor type 2 (CCR2) infiltrate the central and peripheral neural tissues of amyotrophic lateral sclerosis (ALS) patients. To identify the functional role of CCR2+ macrophages in the pathomechanisms of ALS, we used an ALS animal model, mutant Cu/Zn superoxide dismutase 1 G93A (mSOD1)-transgenic (Tg) mice. To clarify the CCR2 function in the model, we generated SOD1 G93A/CCR2 Red fluorescence protein (RFP)/Wild type (WT) /CX3CR1 Green fluorescence protein (GFP)/WT -Tg mice, which heterozygously express CCR2-RFP and CX3CR1-GFP, and SOD1 G93A/CCR2 RFP/RFP-Tg mice, which lack CCR2 protein expression and present with a CCR2-deficient phenotype. In mSOD1-Tg mice, mSOD1 accumulated in the sciatic nerve earlier than in the spinal cord. Furthermore, spinal cords of SOD1 G93A/CCR2 RFP/WT/CX3CR1 GFP/WT mice showed peripheral macrophage infiltration that emerged at the end-stage, whereas in peripheral nerves, macrophage infiltration started from the pre-symptomatic stage. Before disease onset, CCR2+ macrophages harboring mSOD1 infiltrated sciatic nerves earlier than the lumbar cord. CCR2-deficient mSOD1-Tg mice showed an earlier onset and axonal derangement in the sciatic nerve than CCR2-positive mSOD1-Tg mice. CCR2-deficient mSOD1-Tg mice showed an increase in deposited mSOD1 in the sciatic nerve compared with CCR2-positive mice. These findings suggest that CCR2+ and CX3CR1+ macrophages exert neuroprotective functions in mSOD1 ALS via mSOD1 clearance from the peripheral nerves.